(3GOGQI GdLhOI hNOeI GdYedGA (B/s - (3MehO, NVjQ cGXes ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2002)
(3GOGQI GdLhOI GdTGedI,fXGe GOGQI GdLhOI,GSJQGJjLjI GdLhOI GdTGedI,bjGS OQLI GdLhOI,GdQbGHI Ydi GdLhOI,MdbGJ JMSjf GdLhOI,NOeI GdYedGAs
(3HHdhZQGajG U(B.234s
Keywords: (3GdGOGQIs; (3GdQbGHIs; (3LhOI GdGfJGLs